An identity of opposition against urban cosmopolitan setting in Yasmina Khadra's "The attack" (2006) - Mamoto, Retno Sukardan (Wacana, Journal of the Humanities of Indonesia, 2009)
Yasmina Khadra, a female name, pseudonym of Muhammed Moulessehoul, an Algerian military officer for 25 years is now a French citizen. John Cullen translates The attack (2006) from French. Rosenau's post-modernist perspective places the Israel-Palestine conflict in a context of social gap. Israel, a First World, whereas Palestine Third World, are both in the Middle East region. Amin Jaafari and his wife, Sihem, a couple of Arab naturalized citizens of Israel, live in urban cosmopolitan city of Tel Aviv. Opposing Amin's success as a surgeon, Sihem is more attracted to fight for the Palestinian liberation for a homeland. Sihem camouflaged herself with prosthetic pregnancy, blew bombs in a Tel Aviv caf , and died. McLeod's postcolonial point of view places Sihem as a hero. Woodward's concept of identity addresses the Jaafaris' troubled identity. Thus, opposition against urban cosmopolitan setting is the central theme as a notion of identity of that of the protagonists responding to their set situation.